2019
DOI: 10.1088/1748-9326/aafe43
|View full text |Cite
|
Sign up to set email alerts
|

Human dependence on natural resources in rapidly urbanising South African regions

Abstract: Enhancing the governance of social-ecological systems for more equitable and sustainable development is hindered by inadequate knowledge about how different social groups and communities rely on natural resources. We used openly accessible national survey data to develop a metric of overall dependence on natural resources. These data contain information about households' sources of water, energy, building materials and food. We used these data in combination with Bayesian learning to model observed patterns of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Our study provides scope for similar assessments of distributional aspects of environmental justice (sensu Low, 2013) The factors behind these are multiple. First, movement of people from predominantly rural areas to the cities is dominated by relocation to informal settlements, which are often on the margin of the city and are usually not planned development and therefore do not receive all the basic services provided by cities (Balbi et al, 2019), let alone green spaces. Secondly, income plays a major role in who can move to which Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Our study provides scope for similar assessments of distributional aspects of environmental justice (sensu Low, 2013) The factors behind these are multiple. First, movement of people from predominantly rural areas to the cities is dominated by relocation to informal settlements, which are often on the margin of the city and are usually not planned development and therefore do not receive all the basic services provided by cities (Balbi et al, 2019), let alone green spaces. Secondly, income plays a major role in who can move to which Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, these different approaches adopted in studies of ecosystem services do not explicitly consider how ecosystems influence environmental variables such as geomorphology, soils, water availability (rivers, groundwater) and climate, or how local communities may use or value these properties and services. Despite this importance, only a few studies on ecosystem services are set in a broader environmental context (e.g., Egoh et al, 2009;Pettinotti et al, 2018;Balbi et al, 2019). This omission is surprising given the wide literature on the relationship of ecosystem service provision to land degradation (e.g., Smiraglia et al, 2016;Sutton et al, 2016;Tarrasón et al, 2016;Turner et al, 2016;Cerretelli et al, 2018).…”
Section: Environmental Services As a Basis For Understanding Of Soil Food And Water Systems The Nature Of Ecological Environmental Servicmentioning
confidence: 99%
“…Results of the spatial redistribution of UG associated with urban development indicated that cities are facing both opportunities and challenges for urban sustainability. On the one hand, UG became more evenly distributed along the urban-rural gradient, and thereby could potentially provide better access and more equal opportunities for urban dwellers to enjoy outdoor recreation (Niemelä 2014, Tsai et al 2016, Balbi et al 2019. On the other hand, there were greater change in percent cover of greenspace in locations closer to the urban core.…”
Section: The Implications Of Urban Planning and Managementmentioning
confidence: 99%